The interconnection between lipoprotein(a), lipoprotein(a) cholesterol and true LDL-cholesterol in the diagnosis of familial hypercholesterolemia. Issue 6 (December 2020) - Yeang, Calvin; Willeit, Peter; Tsimikas, Sotirios
Abstract : Purpose of review: Elevated levels of lipoprotein(a) [Lp(a)] are present in 30–50% of patients with familial hypercholesterolemia. The contribution of Lp(a) towards risk stratification of patients with familial hypercholesterolemia has been recently recognized, with studies showing a significantly worse prognosis if Lp(a) is elevated. However, the role of elevated Lp(a) in diagnosis of familial hypercholesterolemia is less well defined or accepted. Recent findings: An important confounder in the diagnosis of familial hypercholesterolemia is the significant contribution of the cholesterol content on Lp(a) (Lp(a)-C) in individuals with elevated Lp(a). Because Lp(a)-C is incorporated into all clinical LDL-C measurements, it can contribute significantly to the cholesterol threshold diagnostic criteria for familial hypercholesterolemia used in most clinical algorithms. Summary: In this review, we discuss the interrelationship of Lp(a), Lp(a)-C and correct LDL-C in the diagnosis and prognosis of familial hypercholesterolemia. Future studies of accurately measuring correct LDL-C or in using apoB-100 and Lp(a) criteria may overcome the limitations of using estimated LDL-C in the diagnosis of familial hypercholesterolemia in individuals with concomitant elevation of Lp(a).